Study on the level of intrinsic motivation of Poland`s U-21 Kyokushin karate national team - Piepiora, P. A.; Jaskowska, K. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2025)
Background. In knockdown kumite competition, the willingness to fight and the physical preparation of the competitors are of great importance, with the willingness to fight understood as the intrinsic motivation to confront.